Essentials of dementia : everything you really need to know for working in dementia care - Rahman, Shibley (Jessica Kingsley Publishers, 2018)
To provide high quality dementia care, professionals need to be both knowledgeable about dementia and skilled in the provision of care. This book is an introductory reference guide that will help students, professionals and practitioners develop their skills and expertise to better respond to the needs of people with dementia. It sets out information and advice on essential topics, research and evidence-based practice within dementia care in a clear, sensible way. Based on the standard course structure for higher and further dementia education, this wide-ranging textbook covers topics including dementia diagnosis, person-centred care and law, ethics and safeguarding. The new go-to book for the dementia curriculum, it is an invaluable tool for anyone wishing to improve the required core skills and values needed to care for those affected by dementia.